Identification of Lithocholic Acid and Measurement of Other Bile Acids in Serum of Healthy Humans - Pellizzari, E. D; O’Neil, F. S; Farmer, R. W; Fabre, L. F., Jr (Clinical chemistry (Baltimore, Md.), 1973)
Combined gas—liquid chromatography mass-spectroscopy was used to identify lithocholic acid and confirm the presence of other bile acids in serum of a healthy fasting subject. GLC was used to measure deoxycholic (DCA), chenodeoxycholic (CDCA), and cholic (CA) acids in sera. Before analysis, serum bile acids were purified by (a) enzymatic hydrolysis of conjugates, (b) anion-exchange chromatography, (c) alumina adsorption chromatography, and (d) GLC of methyl trifluoroacetate derivatives on QF-1. Recovery of bile acids (determined by adding [14C]cholic acid to each sample), after correction for loss during purification, was 63-83%. Fasting values for 28 healthy subjects were: 1.4-46.5 (av 7.1), 1.4-49.6 (12.8), and 1.4-46.0 (16.0) µg/100 ml for DCA, CDCA, and CA, respectively. Traces of lithocholic acid were found in 20% of the cases studied. The smaller ranges we found for serum bile acid concentrations in a healthy fasting population are attributed to the careful health-screening of subjects and improved techniques.